2010
DOI: 10.1088/0954-3899/37/10/105105
|View full text |Cite
|
Sign up to set email alerts
|

Toward correction-free8Li(α,n)11B data at the Gamow energy of explosive nucleosynthesis

Abstract: Abstract. The8 Li+ 4 He → 11 B+n reaction inside the center of mass energy region E cm = 0.5 − 2.5 MeV, corresponding to the temperature range T 9 = 1 − 5, is of relevant interest in the fields of nuclear cosmology and nuclear astrophysics. In the context of Big-Bang nucleosynthesis, it has been invoked to overcome the A=8 mass gap; in r-process nucleosynthesis, it is considered a candidate precursor of seed nuclei. In this experimental work, the cross section, summed over all 11 B final bound states, at the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 35 publications
(240 reference statements)
0
20
0
Order By: Relevance
“…Although the 8 Li(α, n) 11 B cross section has been measured by several groups (see Ref. [10] and references therein) there is still a significant discrepancy between the measurements (see, for example, Fig. 4 of Ref.…”
Section: Astrophysical Reaction Ratementioning
confidence: 99%
See 1 more Smart Citation
“…Although the 8 Li(α, n) 11 B cross section has been measured by several groups (see Ref. [10] and references therein) there is still a significant discrepancy between the measurements (see, for example, Fig. 4 of Ref.…”
Section: Astrophysical Reaction Ratementioning
confidence: 99%
“…[9] and references therein) and has been investigated by various groups (see, for example, Ref. [10] and references therein). More recently, it was suggested that this reaction could also affect r-process nucleosynthesis [11].…”
Section: Introductionmentioning
confidence: 99%
“…Also, radioactive beams provide a probe of the nuclear structure, in unusual conditions of excitation energy and isospin. Many experiments have been performed in recent decades with various beams of halo nuclei such as 6 He, 11 Be, 8 He or 11 Li (see references in Ref. [2]).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the 8 Li(α,n) 11 B reaction could affect the non-standard Big-Bang nucleosynthesis (see Ref.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation